Predation on Biomphalaria sp. (Mollusca: Planorbidae) by three species of the genus Belostoma (Heteroptera: Belostomatidae) - Armúa de Reyes, C. A. (2006)
The voracious behaviour of water bugs is well known as they attack a great diversity of invertebrate and vertebrate organisms which may be of various sizes, even larger than they are (Schnack, 1976; Menke, 1979). All of the Belostomatidae family members have forelegs adapted to catch prey which are usually ambushed by bugs. After catching prey, bugs handle it in order to insert their piercing mouth parts to inject saliva and liquefy prey’s tissues to suck. (Párrafo extraído del texto a modo de resumen)